2019
DOI: 10.1097/pas.0000000000001388
|View full text |Cite
|
Sign up to set email alerts
|

Denosumab-treated Giant Cell Tumors of Bone: A Clinicopathologic Analysis of 35 Cases From the French Group of Bone Pathology

Abstract: Denosumab, an antibody directed against receptor activator of nuclear factor-κB ligand (RANKL), has recently been introduced in the treatment strategy of giant cell tumor of bone. In this study, we assessed the tumor changes induced by denosumab in a national multicentric series of 35 cases (French Bone Pathology Group network—ResOs). Tissue specimens collected before and after denosumab treatment were investigated for RANKL, H3.3 G34W, p63, and Ki-67 expression, and for H3F3A mutation. These parameters were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 27 publications
4
32
0
4
Order By: Relevance
“…The multinucleated giant cells disappear, and the lesional mononuclear cells decrease and partly transform into osteoblasts forming varying amounts of immature woven bone trabeculae. 3,4 This observation is in line with gene expression profiles of the mononuclear component of GCT that resemble those of cells with early osteoblastic differentiation. 5 In some cases, reactive atypia can be striking and mimic malignant transformation.…”
Section: Gross and Microscopic Featuressupporting
confidence: 72%
“…The multinucleated giant cells disappear, and the lesional mononuclear cells decrease and partly transform into osteoblasts forming varying amounts of immature woven bone trabeculae. 3,4 This observation is in line with gene expression profiles of the mononuclear component of GCT that resemble those of cells with early osteoblastic differentiation. 5 In some cases, reactive atypia can be striking and mimic malignant transformation.…”
Section: Gross and Microscopic Featuressupporting
confidence: 72%
“…The efficacy and safety of denosumab for GCTB treatment have been reported, and the U.S. Food and Drug Administration approved the use of denosumab in 2013 [ 14 ]. However, 12 cases of malignant transformation of GCTB during and after denosumab treatment have been reported [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], suggesting that denosumab treatment is associated with malignant transformation [ 33 ]. According to recent systematic reviews, the cumulative incidence of secondary malignant GCTB without a history of radiotherapy or denosumab treatment was 0.6% [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al [ 16 ] have observed that malignant transformation occurred in 1 of 25 patients (4%) after a median follow-up of 27 months after denosumab was administered for 8 months postoperatively. Treffel et al [ 23 ] have revealed that, among 35 patients who presented with GCTB and received denosumab treatment, malignant transformation occurred in one patient (2.9%), 18 months postoperatively. Recently, Perrin et al [ 21 ] have reported that malignant transformation occurred in one of 25 patients (4%) with GCTB at a median follow-up of 57 months after denosumab administration, 55 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Denosumab, a RANK ligand inhibitor, is frequently used now in the treatment of GCTB, especially for unresectable tumors. 27 , 28 Favorable outcome following its use have been reported 46 , 47 but some recent studies reported otherwise. 48 , 49 By multivariate analysis, our study shows that denosumab therapy increases the risk for local recurrence as a significant trend level ( P = 0.053).…”
Section: Discussionmentioning
confidence: 99%